Structure Design and Analysis of a New Kind of Composite Climbing-ladder Wheelchair - Gen Xiong; Hua Zhang; Yilin Zhou; Shuai You; Zhijun Shang (Jixie chuandong)
In order to solve the difficulty in climbing stairs for the elderly and disabled， a new type of combined climbing wheelchair with planet wheel track is proposed. The combined structure with planet wheel track is used to achieve the function of stair-climbing and obstacle-surmounting. The wheelchair is driven by a motor， the planet wheel adopts chain drive to climb stairs and drive on the flat ground. Combined with the track device， this structure effectively reduces the vibration of the wheelchair with planet chair and improves the obstacle-surmounting ability of traditional wheelchair. On the basis of comparing the structural characteristics of the existing climbing wheelchair， the scheme of designing a new type wheelchair robot with a combination of with the planet wheel and track is introduced， and its operating principle is analyzed， a mathematical model is established to make a kinematics and dynamics analysis on the stair-climbing process. The results show that， the wheelchairs can safely climb most stairs. The structure design of the wheelchair is reasonable， the combination of climbing stairs and moving on the flat ground is realized.